Mendorong Kewirausahaan Mahasiswa: Program Pendampingan Pengembangan Usaha ‘Jaemur Crispy’ - Suryani, Pesi; Daurrohmah, Eka Wirajuang; Gaol, Lasando Lumban; Puspitasari, Nindya Farah Dwi; Robiansyah, Anton; Rahmawati, Anisa; Yulianto, Krist Setyo; Oktari, Vivi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This community service activity focuses on developing the micro-enterprise, Jaemur Crispy, managed by Anisa Rahmawati, a university student. The main issues faced are the lack of knowledge in business management and marketing. The purpose of this activity is to improve managerial and marketing skills through intensive mentoring. The method used is a participatory approach, which includes training, group discussions, and direct mentoring in business management. The results of this activity show a significant increase in sales, with a 30% rise during the first three months after the training, along with improvements in business management and a growing entrepreneurial awareness among students. Additionally, this program successfully fostered local leaders capable of driving social change within their community. Thus, this activity provides a sustainable positive impact on entrepreneurial development within the student environment.